2013 Norchip 2013
DOI: 10.1109/norchip.2013.6702017
|View full text |Cite
|
Sign up to set email alerts
|

Modeling and predistortion of envelope tracking power amplifiers using a memory binomial model

Abstract: Nowadays envelope tracking (ET) is considered one of the most appealing techniques for the efficiency enhancement of RF power amplifiers (PAs), but it also introduces a number of additional challenges for the system simulation and implementation. In this context, this paper aims to provide a new behavioral model capable of an improved performance when used for the modeling and predistortion of RF PAs deployed in ET transceivers. The proposed solution consists in a 2D behavioral model having as a dual-input the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…First, a 2D polynomial structure with memory is proposed, named Memory Binomial Model after its structure inspired by binomial power series [20]. Secondly a different approach is proposed, where the Cann model for RF PAs is extended including the new independent variable V ENV and defining new functions for modeling of dynamic AM/AM and AM/PM distortion effects [21].…”
Section: Behavioral Models For Envelope Tracking Power Amplifiersmentioning
confidence: 99%
See 3 more Smart Citations
“…First, a 2D polynomial structure with memory is proposed, named Memory Binomial Model after its structure inspired by binomial power series [20]. Secondly a different approach is proposed, where the Cann model for RF PAs is extended including the new independent variable V ENV and defining new functions for modeling of dynamic AM/AM and AM/PM distortion effects [21].…”
Section: Behavioral Models For Envelope Tracking Power Amplifiersmentioning
confidence: 99%
“…The comparison among the Generalized Memory Polynomial [28], the Envelope Memory Polynomial [29] and the static polynomial showed that the addition of memory compensation capabilities was not able to improve the PA ACPR, while a small improvement was observed in terms of NMSE and EVM compared to the static polynomial DPD. In this journal we present linearization results obtained using a 2D-DPD architecture based on the same concept [20]. The proposed predistortion scheme is showed in Fig.…”
Section: Digital Predistortion Of Envelope Tracking Power Amplifiersmentioning
confidence: 99%
See 2 more Smart Citations
“…The reference [1] offers an exhaustive list referencing some of the most interesting works. Some recent ET publications focus on the compensation of the memory effects [1][2][3][4]. Unfortunately, it's not always easy to implement such compensations, because of the difficulties in characterizing the memory effects.…”
Section: Introductionmentioning
confidence: 99%